A random dynamical systems perspective on stochastic resonance. (7th June 2017) - Maria Cherubini, Anna; Lamb, Jeroen S W; Rasmussen, Martin; Sato, Yuzuru
Abstract: We study stochastic resonance in an over-damped approximation of the stochastic Duffing oscillator from a random dynamical systems point of view. We analyse this problem in the general framework of random dynamical systems with a nonautonomous forcing. We prove the existence of a unique global attracting random periodic orbit and a stationary periodic measure. We use the stationary periodic measure to define an indicator for the stochastic resonance.